2016
DOI: 10.1001/jamasurg.2016.2783
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Cost-effectiveness in the Veterans Affairs Open vs Endovascular Repair Study of Aortic Abdominal Aneurysm

Abstract: clinicaltrials.gov Identifier: NCT00094575.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…9e11 Two main points may be noted in this clinical problem: the first point is whether the early survival benefit and shorter hospital stay of EVAR offset the high device costs and more frequent reinterventions and the second point is that health-care system and socioeconomic background differ between countries. 9,10 Epstein et al reviewed four major randomized clinical trials: EVAR-1 (United Kingdom), Dutch Randomized Endovascular Aneurysm Management (DREAM, the Netherlands), Open versus Endovascular Repair (OVER, USA), and Anevrysme de l'aorte abdominale, Chirurgie versus Endoprothese (ACE, France) and concluded that EVAR was not cost-effective in the midterm to long term based on the data from the EVAR-1, DREAM, and ACE trials, but might be cost-effective based on the OVER trial. However, even in the OVER trial, the longterm results did not show the overall superiority of EVAR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9e11 Two main points may be noted in this clinical problem: the first point is whether the early survival benefit and shorter hospital stay of EVAR offset the high device costs and more frequent reinterventions and the second point is that health-care system and socioeconomic background differ between countries. 9,10 Epstein et al reviewed four major randomized clinical trials: EVAR-1 (United Kingdom), Dutch Randomized Endovascular Aneurysm Management (DREAM, the Netherlands), Open versus Endovascular Repair (OVER, USA), and Anevrysme de l'aorte abdominale, Chirurgie versus Endoprothese (ACE, France) and concluded that EVAR was not cost-effective in the midterm to long term based on the data from the EVAR-1, DREAM, and ACE trials, but might be cost-effective based on the OVER trial. However, even in the OVER trial, the longterm results did not show the overall superiority of EVAR.…”
Section: Discussionmentioning
confidence: 99%
“…However, even in the OVER trial, the longterm results did not show the overall superiority of EVAR. 10 The update report revealed lower costs of EVAR at the initial aneurysm repair but higher costs for outpatient visits, imaging studies, and secondary intervention, which eliminated the superiority of EVAR during initial repair. 10 A systematic review conducted by van Bochove et al 11 analyzed 13 studies with economic evaluations between 1999 and 2014 and found that the cost-effectiveness of EVAR compared with OS was inconsistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Against this background, four major, non-industry sponsored randomized trials were conducted from 1999–2009 to compare the results of elective open repair and EVAR in patients who were medically and anatomically suitable for either procedure, including the EVAR-1 trial 32 34 , the Dutch Randomized Endovascular Aneurysm Management trial (DREAM) 35 38 , the Open Versus Endovascular Repair trial (OVER) 39 43 , and the Anevrysme de l’aorte abdominale: Chirurgie versus Endoprothese trial (ACE) 44 . Two demographic features of these trials were different from the earlier small aneurysm trials: only 5.6% of the patients were women and the AAAs were larger, with mean diameters ranging from 5.5 cm in ACE to as much as 6.5 cm in EVAR-1.…”
Section: Elective Evar Versus Open Repairmentioning
confidence: 99%
“…Type II endoleaks were likely to be associated with AAA expansion when discovered later than 1 year after EVAR ( p <0.0001), though 84% of all type II endoleaks were detected earlier and 60% of them resolved spontaneously. Despite the expense of CT scan surveillance and re-interventions, OVER still found that EVAR was cost effective compared to open repair 42 , 43 . This was not the case in EVAR-1 33 , in DREAM 38 , or in Markov models derived from all four trials 46 .…”
Section: Elective Evar Versus Open Repairmentioning
confidence: 99%